Bulk and single-molecule analysis of a bacterial DNA2-like helicase–nuclease reveals a single-stranded DNA looping motor. Issue 14 (4th July 2020) - Wilkinson, Oliver J; Carrasco, Carolina; Aicart-Ramos, Clara; Moreno-Herrero, Fernando; Dillingham, Mark S
Abstract: DNA2 is an essential enzyme involved in DNA replication and repair in eukaryotes. In a search for homologues of this protein, we identified and characterised Geobacillus stearothermophilus Bad, a bacterial DNA helicase–nuclease with similarity to human DNA2. We show that Bad contains an Fe-S cluster and identify four cysteine residues that are likely to co-ordinate the cluster by analogy to DNA2. The purified enzyme specifically recognises ss-dsDNA junctions and possesses ssDNA-dependent ATPase, ssDNA binding, ssDNA endonuclease, 5′ to 3′ ssDNA translocase and 5′ to 3′ helicase activity. Single molecule analysis reveals that Bad is a processive DNA motor capable of moving along DNA for distances of >4 kb at a rate of ∼200 bp per second at room temperature. Interestingly, as reported for the homologous human and yeast DNA2 proteins, the DNA unwinding activity of Bad is cryptic and can be unmasked by inactivating the intrinsic nuclease activity. Strikingly, our experiments show that the enzyme loops DNA while translocating, which is an emerging feature of processive DNA unwinding enzymes. The bacterial Bad enzymes will provide an excellent model system for understanding the biochemical properties of DNA2-like helicase–nucleases and DNA looping motor proteins in general.